Unique Case of Squatter Prevention Projects in Turkey: the Tozkoparan Neighbourhood, Istanbul - Soher, Sebnem; Akpinar, Ipek (International Planning History Society Proceedings, 2016)
Istanbul is a metropolitan city, owing the foundations of its physical form to many harsh urban decisions made through the 1950's. Rapid urbanization and internal immigrations, caused an urgent need of housing resulted in an uncontrolled, unplanned growth of the city. The public authorities, constrained by an inertia, offered only limited solutions to shelter the urban poor. Instead, the public investments were assigned to the construction of new highways and housing for middle to upper middle class. Old neighbourhoods in the historic center of the city were torn apart in order to accommodate a new, automobile-based life style and many former residents of the city had to be evicted and relocated. Tozkoparan neighbourhood, the case study investigated in this paper, is the first example of “Squatter Prevention Projects”, an exception to the urban conditions, as it is a public housing project intended to shelter those evicted from their houses or incapable to dwell in formal houses. Among a limited number of projects countrywide, Squatter Prevention Projects were made possible with the Squatter Act of 1966. Yet with the shifting urban politics after 1980's, these projects become the target of a new, urban renewal discourse, which would result in a radical transformation of the neighbourhoods. An investigation across changing housing politics in Turkey shows firstly the state organizations' late attempt to deal with the internal immigration and an unplanned expansion of illegal neighbourhoods. The immigration provided the required labour power for the growing city, yet the housing policies could not manage the increase of urban population. A big part of the new inhabitants had to find their own solution. Finally the social state was able to provide the necessary investment into social housing. The case study also reveals that it has been a critical point in the urban planning history of Turkey, the attempt of becoming a social state was interrupted by military coups and newly introduced neoliberal politics. Our paper, at first, briefly depicts the Act of 1966 and the Tozkoparan Project. Secondly, offering a short overview of the last 40 years of the neighbourhood, deals with the emerging issue of the so-called liberal policies against the urban poor. The spatial interventions done by the inhabitants through this period are also considered as an important aspect of this overview. Respectively many of the appropriations show the lack of certain qualities in the planning of the project.